A composite high-frame-rate system for clinical cardiovascular imaging - Shougang Wang; Wei-ning Lee; Provost, J.; Jianwen Luo; Konofagou, E.E. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2008)
High frame-rate ultrasound RF data acquisition has been proved to be critical for novel cardiovascular imaging techniques, such as high-precision myocardial elastography, pulse wave imaging (PWI), and electromechanical wave imaging (EWI). To overcome the frame-rate limitations on standard clinical ultrasound systems, we developed an automated method for multi-sector ultrasound imaging through retrospective electrocardiogram (ECG) gating on a clinically used open architecture system. The method achieved both high spatial (64 beam density) and high temporal resolution (frame rate of 481 Hz) at an imaging depth up to 11 cm and a 100% field of view in a single breath-hold duration. Full-view imaging of the left ventricle and the abdominal aorta of healthy human subjects was performed using the proposed technique in vivo. ECG and ultrasound RF signals were simultaneously acquired on a personal computer (PC). Composite, full-view frames both in RF- and B-mode were reconstructed through retrospective combination of seven small (20%) juxtaposed sectors using an ECG-gating technique. The axial displacement of the left ventricle, in both long-axis and short-axis views, and that of the abdominal aorta, in a long-axis view, were estimated using a RF-based speckle tracking technique. The electromechanical wave and the pulse wave propagation were imaged in a cineloop using the proposed imaging technique. Abnormal patterns of such wave propagation can serve as indicators of early cardiovascular disease. This clinical system could thus expand the range of applications in cardiovascular elasticity imaging for quantitative, noninvasive diagnosis of myocardial ischemia or infarction, arrhythmia, abdominal aortic aneurysms, and early-stage atherosclerosis.